Real-World Comparisons of Low-Dose NOACs versus Standard-Dose NOACs or Warfarin on Efficacy and Safety in Patients with AF: A Meta-Analysis - Ze Li (Cardiology Research and Practice, 2022)
Objective. We aimed to further investigate the efficacy and safety of low-dose NOACs by performing a meta-analysis of cohort studies. Background. Meta-analyses of randomized controlled trials (RCTs) have demonstrated that low-dose non-vitamin K antagonist oral anticoagulants (NOACs) showed inferior efficacy compared with standard-dose NOACs, although they are still frequently prescribed for patients with atrial fibrillation (AF) in the clinical practice. Methods. Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and MEDLINE were systematically searched from the inception to September 9, 2021, for cohort studies that compared the efficacy and/or safety of low-dose NOACs in patients with AF. The primary outcomes were ischemic stroke and major bleeding, and the secondary outcomes were mortality, intracranial hemorrhage (ICH), and gastrointestinal hemorrhage (GH). Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated with the random-effect model. Results. Twenty-five publications involving 487856 patients with AF were included. Compared with standard-dose NOACs, low-dose NOACs had comparable risks of ischemic stroke (HR = 1.03, 95% CI 0.96 to 1.11), major bleeding (HR = 1.12, 95% CI 0.97 to 1.28), ICH (HR = 1.09, 95% CI 0.88 to 1.36), and GH (HR = 1.11, 95% CI 0.92 to 1.33), except for a higher risk of mortality (HR = 1.41, 95% CI 1.21 to 1.65). Compared with warfarin, low-dose NOACs were associated with lower risks of ischemic stroke (HR = 0.72, 95% CI .67 to 0.78), mortality (HR = 0.67, 95% CI 0.59 to 0.77), major bleeding (HR = 0.64, 95% CI 0.53 to 0.79), ICH (HR = 0.57, 95% CI 0.42 to 0.77), and GH (HR = 0.78, 95% CI 0.64 to 0.95). Conclusions. Low-dose NOACs were comparable to standard-dose NOACs considering risks of ischemic stroke, major bleeding, ICH, and GH, and they were superior to warfarin. Low-dose NOACs might be prescribed effectively and safely for patients with AF. Considering limitations, further well-designed prospective studies are foreseen.